2018
DOI: 10.1007/jhep08(2018)053
|View full text |Cite
|
Sign up to set email alerts
|

On multi-spin classical strings with NS-NS flux

Abstract: We study multi spin semiclassical strings in AdS 3 × S 3 × T 4 background supported by a mixture of Neveu-Schwarz-Neveu-Schwarz (NS-NS) and Ramond-Ramond (R-R) fluxes. This 'mixed flux' background has been recently proved to be classically integrable. We start with a particular rigidly spinning fundamental string in AdS 3 × S 1 coupled to the NS-NS flux and classify the possible profiles. We also find out how the scaling relation among the energy and angular momenta of such a string changes due to presence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 112 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…All of it started as the 'Giant Magnon' dispersion relation was proposed in [44], which turned out to have non-periodic contribution in the momentum as the periodicity is explicitly spoiled by the flux. Subsequently finite-gap solutions were proposed in [49,50] and a large class of folded [51], rotating [52,53,54], pulsating [55,56] and GKP-like multi-spike [57,58] strings have been studied in the literature. Also, well known Neumann-Rosochatius dynamical model of strings has been generalised to AdS 3 × S 3 with NS-NS fluxes together with relevant classical solutions [59,60,61] and one-loop quantization [62] being elucidated in a large number of papers.…”
Section: Introductionmentioning
confidence: 99%
“…All of it started as the 'Giant Magnon' dispersion relation was proposed in [44], which turned out to have non-periodic contribution in the momentum as the periodicity is explicitly spoiled by the flux. Subsequently finite-gap solutions were proposed in [49,50] and a large class of folded [51], rotating [52,53,54], pulsating [55,56] and GKP-like multi-spike [57,58] strings have been studied in the literature. Also, well known Neumann-Rosochatius dynamical model of strings has been generalised to AdS 3 × S 3 with NS-NS fluxes together with relevant classical solutions [59,60,61] and one-loop quantization [62] being elucidated in a large number of papers.…”
Section: Introductionmentioning
confidence: 99%
“…This model then interpolates between the AdS 3 background with R-R flux which can be studied by the integrability approach and the background with pure NS-NS flux which can be studied using the usual WZW model. To build the bridge, numerous string solutions have been studied in detail in this so called mixed flux background [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…This periodic ansatz is closely related to the ansatz introduced in [3] to transform the analysis of the energy spectrum of circular strings spinning in AdS 5 ×S 5 into the study of periodic solutions to the Neumann-Rosochatius integrable system, which is a model of oscillators on a sphere. In reference [4] it was shown that the analysis of closed strings spinning in AdS 3 × S 3 × T 4 with a mixture of Ramond-Ramond (R-R) and Neveu-Schwarz-Neveu-Schwarz (NS-NS) three-form fluxes can be performed by means of an integrable deformation of the Neumann-Rosochatius mechanical system (see [5]- [31] for other solutions and various problems regarding the integrability of the AdS 3 /CFT 2 correspondence with mixed fluxes). The purpose of the present article is to extend the approach of [2] to find minimal area surfaces ending on two concentric circumferences in the presence of NS-NS flux using the integrable deformation of their associated mechanical system.…”
Section: Introductionmentioning
confidence: 99%